ANALYSIS OF THE IMPACT OF CIRATA FLOATING SOLAR POWER PLANT INTEGRATION ON THE VOLTAGE STABILITY OF THE 500 kV JAVA-BALI SYSTEM - Abidin, Dimas Zainal; Krismanto, Awan Uji; Wartana, I Made (Journal of Sustainable Technology and Applied Science (JSTAS), 2025)
This study analyses the impact of integrating a solar photovoltaic power plant (PLTS) on the voltage stability of the 500 kV Java-Bali transmission system, with a case study on the Cirata Floating Solar Power Plant. With the increasing use of renewable energy, particularly solar PV, it is crucial to understand how the integration of this variable energy source affects the reliability and stability of the power system. The Cirata Floating Solar Power Plant, the largest of its kind in Asia, has a capacity of 145 MW AC or equivalent to 192 MWp. However, integrating the Cirata Floating Solar Plant into the transmission system may potentially affect voltage stability, necessitating an in-depth analysis to assess its impact. The methodology employed in this study includes static voltage analysis through PV curve evaluation and dynamic voltage analysis to determine the system's capability to maintain or restore voltage within permissible stability limits. The study utilises DigSILENT PowerFactory software to simulate system conditions before and after the PLTS integration. The results indicate that the Cirata Floating Solar Plant’s power injection of 192 MWp improves voltage quality and enhances system stability compared to the pre-integration conditions.